Escherichia coli Fails to Efficiently Maintain the Activity of an Important Flavin Monooxygenase in Recombinant Overexpression - Milker, Sofia; Goncalves, Leticia C. P.; Fink, Michael J.; Rudroff, Florian (Frontiers in Microbiology, 2017)
This paper describes the measurement and analysis of in vivo activity and stability of cyclohexanone monooxygenase from Acinetobacter sp. NCIMB 9871 (CHMO), a model Baeyer-Villiger monooxygenase, in the recombinant host Escherichia coli. This enzyme was often described as poorly stable in vitro, and has recently been found to deactivate rapidly in the absence of its essential cofactors and anti-oxidants. Its stability in vivo was scarcely studied, so far. Under conditions common for the overexpression of CHMO we investigated the ability of the host to support these properties using metabolomics. Our results showed that E. coli failed to provide the intracellular levels of cofactors required to functionally stabilize the enzyme, although the biocatalyst was produced in high concentration, and was invariably detected after protein synthesis had stopped. We thus infer that biotechnological applications of CHMO with this host relied on a residual activity of approx. 5-10%. Other microorganisms might offer a more efficient solution for recombinant production of CHMO and related enzymes.